Aspek Klinik Penggunaan Kortikosteroid Topikal - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1985)
The most exciting therapeutic advance in the history of dermatological therapy has been the discovery of topical corticosteroids. At this moment these compounds constitute the major part of treatment of many skin diseases. When used correctly, they are invaluable, but when used indiscriminately where a definite diagnosis has not been made they can mask the clinical feature of the disease and lead to many side effects. This paper reviews literature relevant to the clinical use of topical steroids. The mechanism of actions, classification, the action influencing factors, and side effects of the topical steroid have been described.